Librarianship in developing countries - Guruswamy Naidu, N., 1937- (New Delhi : Ess Ess, 1992)
Seminar papers; with reference to India.
Includes index.
Includes bibliographical references.
Keywords: Library science -- India -- Congresses; Library science -- Developing countries -- Congresses